Designing STIBs and ToC Frameworks for Learning Labs - Jain, Harsha; Chadha, Deepali; Gartaula, Hom N.; Mukhopadhyay, Prama; Goel, Kritika; Dwevedi, Anusha; Shivhare, Richa; Puskur, Ranjitha (CGIAR System Organization, 2024)
As a continuation of the work done in previous workshops conducted for the LLs led by IRRI, another workshop was conducted in Delhi on 27-28 November 2023.